Effect of antibiotics on inflammatory marker (IL-6) and perinatal outcomes in women with preterm premature rupture of membranes - Arora, Ashima; Biswas, Ratna; Dubey, Bhawna; Goswami, Binita; Saxena, Sonal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim is to study the effect of antibiotics on inflammatory marker (IL-6) and perinatal outcomes in women with preterm premature rupture of membranes (PPROM). Methods: 60 women with PPROM at 28–34 weeks of gestation were enrolled in the study. All the women were given antibiotics as per hospital protocol and were subjected to blood sampling for Interleukin -6(IL-6) at admission, delivery and umbilical cord blood. IL-6 levels were assessed for associations with adverse perinatal outcomes and the effect of antibiotic treatment on IL-6 and perinatal outcomes were studied. The data were analyzed using t test and χ2 test. Results: Increased level of IL-6 was associated with chorioamnionitis and neonatal sepsis (p<0.001). High level of IL-6 led to early delivery and complete course of antibiotics suppressed IL-6 (p<0.001) and clinical chorioamnionitis in women with PROM. Full course of antibiotics also decreased the admission rate of babies to neonatal intensive care unit and suppressed respiratory distress syndrome, neonatal sepsis. Conclusions: Increased level of IL-6 is seen in women with chorioamnionitis and neonatal sepsis. Antibiotics suppress the IL-6 levels, chorioamnionitis and neonatal sepsis.